Solanum tuberosum A Promising Crop for Starvation Problem - Yildiz, Mustafa; Ozgen, Yasin (IntechOpen, 2021)
Potato (Solanum tuberosum L.) is the fourth-largest food crop produced in the world with approximately 370 million tonnes. This product is a staple in many diets throughout the world and the underground swollen tubers of the plant are rich sources of proteins, carbohydrates, minerals (K, Mn, Mg, Fe, Cu and P), and vitamins (C, B1, B3, B6, K, folate, pantothenic acid). Improvement of new potato cultivars resistant to biotic and abiotic factors is extremely important, as these are the main reasons for decreased potato production. Seed tuber production and tuber storage under healthy conditions after harvest are two important issues in potato cultivation. As such, this book discusses the importance of the potato plant and examines ways to increase its production and develop new cultivars resistant to stress factors via conventional and biotechnological methods.